2008
DOI: 10.5194/acpd-8-2745-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personal UV exposure on a ski-field at an alpine site

Abstract: Abstract. Mountain sites experience enhanced ambient UV radiation levels due to the concurrent effects of shorter radiation path-length, low aerosol load and high reflectivity of the snow surfaces. This study was encouraged by the possibility to collect data of personal UV exposure in the mountainous areas of Italy, for the first time. Personal UV exposure (expressed in terms of Exposure Ratio, ER) of two groups of volunteers (ski instructors and skiers) at the Alpine site of La Thuile (Valle d'Aosta region, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…D 3 in the human body) we need information of weighted UV irradiance on arbitrarily oriented surfaces because of highly variable orientation of the human body relative to solar radiation. There are case studies or short campaign focusing on insolation over various parts of the human body that is inferred from the PS badges attached to manikin (e.g., Downs and Parisi, 2007) or human beings (e.g., Siani et al, 2007). The monitoring of UV exposures over longer periods and over many sites is complex issue.…”
Section: Discussionmentioning
confidence: 99%
“…D 3 in the human body) we need information of weighted UV irradiance on arbitrarily oriented surfaces because of highly variable orientation of the human body relative to solar radiation. There are case studies or short campaign focusing on insolation over various parts of the human body that is inferred from the PS badges attached to manikin (e.g., Downs and Parisi, 2007) or human beings (e.g., Siani et al, 2007). The monitoring of UV exposures over longer periods and over many sites is complex issue.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, by the same group, on skiers at a high albedo alpine site found even higher ER values on the forehead, with a median ER of 60%, and sometimes even exceeding 100%. 123 However, large ER values are the exception rather than the rule for the wider population.…”
Section: Personal Exposure To Uv Radiationmentioning
confidence: 99%
“…D 3 in human body) we need information of weighted UV irradiance on arbitrarily oriented surfaces because of highly variable orientation of human body relative to solar radiation. There are case studies or short campaigns focusing on insolation over various parts of human body that is inferred from PS badges attached to manikin (e.g., Downs and Parisi, 2007) or human beings (e.g., Siani et al, 2007). Monitoring of human UV exposure over longer periods and over many sites is complex issue.…”
Section: Egumentioning
confidence: 99%